How much change in symptoms do spinal surgeons expect following lumbar decompression and microdiscectomy?. (September 2021) - Anderson, David B.; Stanford, Ralph; Van Gelder, James M.; Harris, Ian A.; Eyles, Jillian; Damodaran, Omprakash; Maher, Christopher G.; Ferreira, Manuela L.
Highlights: Australian spine surgeons prefer full laminectomy (58%; N = 41) for treating central lumbar spinal stenosis, with open unilateral laminotomy and cross-over decompression (25%; N = 18) the second most preferred. Australian spine surgeons expect on a +/− 100% change scale a mean improvement of 86% (SD: 8.7) in patients' neurogenic claudication by 3 months post lumbar decompression. Australian spine surgeons expect on a +/− 100% change scale an improvement of 89% (SD: 8.5) in patients' radicular leg pain following microdiscectomy. More than half (55%) of Australian spine surgeons accurately reported the current evidence supporting lumbar decompression with fusion (compared with non-surgical care) compared with one-third (35%) for lumbar decompression alone (compared with non-surgical care). Abstract: The study aimed to determine how much change in neurogenic claudication spinal surgeons expect in patients following lumbar decompression for lumbar spine stenosis (LSS), and radicular leg pain following microdiscectomy. Secondary aims were to identify surgeons' preferences regarding surgical techniques for lumbar decompression, and their rating of the quality of current evidence for lumbar decompression. All Australian spine surgeons were invited, of whom 71 completed the survey (31% response rate). Only registered spinal surgeons were included. The online survey, administered using REDCap, included 4 sections: demographics and background; expected change in symptoms on a +/− 100% scale (−100% worst, 0% no change and 100% best possible); surgical preference; and rating of current evidence for lumbar decompression compared with other treatments. There were 71 complete responses, 76% were neurosurgeons (N = 54), predominantly male (96%; N = 68). On average, surgeons expected an 86% (median: 87%, inter-quartile range (IQR): 80%, 91%) improvement in neurogenic claudication following lumbar decompression for LSS and 89% (median: 91%, IQR: 85%, 95%) improvement in radicular pain following microdiscectomy. A multiple linear regression found no surgeon characteristics were associated with expected change following surgery. The preferred surgical technique for LSS was full laminectomy (58%; N = 41). Thirty-five percent of surgeons accurately rated the evidence supporting the superiority of lumbar decompression compared with non-surgical care for LSS as low quality. Spine surgeons expect large symptom improvements following lumbar decompression and microdiscectomy. Understanding of the current evidence was higher for lumbar decompression with fusion, than for decompression alone for LSS.